Project finance - Trigoso Suárez, Marco Antonio (2018)
Both private and public activities play a transcendent role for the implementation of projects in which project finance is used as a financing system. The links will be given at all times, since the VPS is constituted as it will need to be registered in the register of legal entities for its operation; the project will also require various authorizations, for example those required under the competition regime; as well as licenses issued by municipalities, regional or central governments; the administration is also present regarding the tax regime and the corresponding tax payment; even, in some cases, the State determines change control; In addition, governments have a vital influence on political risk or country risk, which implies an area of evaluation that the promoters make regarding the stability of the project over time.